Association of Antepartum Blood Pressure and Angiogenic Profile in Women With Chronic Hypertension [3OP]. (May 2018) - Minhas, Ruby; Perdigao, Joana; Nasim, Rabab; Mueller, Ariel; Young, Danielle; Rana, Sarosh
Abstract : INTRODUCTION: This pilot study explored the association between antenatal blood pressure (BP) and angiogenic biomarkers (sFlt and PlGF) at delivery among women with chronic hypertension (cHTN). METHODS: Blood samples were collected within 96 hours of delivery. Mean outpatient BP was stratified as controlled (cBP<140/90) or uncontrolled (uBP≥140/90). Angiogenic factors were measured on an automated platform. Descriptive statistics were assessed with Wilcoxon Rank Sum or chi-square tests, as appropriate. Logistic regression was employed to assess for adverse pregnancy outcomes. RESULTS: Of the 78 women enrolled, 58 (74.3%) were African American and 22 (28.2%) had uBP. There was no difference between cBP and uBP in age, race, ethnicity, BMI, smoking/substance abuse, parity, or previous preeclampsia (preE) diagnosis. A higher proportion cBP patients did not use a HTN agent (46.4% vs 13.6%, P =.01), although aspirin usage did not differ. Women with uBP had higher levels of sFlt1 and sFlt1/PlGF (sFlt: 4218.5 vs 3056.0 pg/mL, P =.046; sFlt/PlGF: 62.5 vs. 25.0, P =.04). A greater proportion of uBP vs. cBP patients had superimposed (SI) preE with severe features (preE-SF) (54.6% vs. 25.0%; P =.01), preterm delivery (40.9% vs. 10.7%; P =.002), and more admissions to rule out preE (77.3% vs. 30.4%; P =.0002). In the multivariable model, women with uBP had greater odds of preterm delivery (OR: 6.78; P =.01), SI preE (OR: 3.20; P =.03) and SI preE-SF (OR: 3.27; P =.04). CONCLUSION: Antepartum control of BP is associated with a favorable angiogenic profile at delivery and improved outcomes among women with cHTN. Larger studies are needed to confirm these findings.